Strategy of BMT Makmur Mandiri Sukoharjo in Maintaining Liquidity During the Pandemic - Fauzul Hanif Noor Athief; Darlin Rizki; Bela Septiana Wahyu Priyadika; Sausan Liski Aulia (Universitas Negeri Gorontalo, 2023)
The purpose of this study was to find out what steps were taken by BMT Makmur Mandiri Sukoharjo in maintaining liquidity during the Pandemic Covid-19. The researcher uses a qualitative research type and the approach used is a case study, research that explores individuals, groups, institutions, and so on within a certain time. Data were collected by interviewing the BMT management, observing the institution, and collecting the necessary documentation. Based on this research, it shows that the way BMT Makmur Mandiri Sukoharjo maintains smoothness and balance between income and expenditure is by cutting less important needs, including development costs that must be canceled as well as promotional budgets that must be trimmed and saving funds to maintain liquidity of BMT Makmur Mandiri Sukoharjo.